Genome Characterization of mcr-1–Positive Escherichia coli Isolated From Pigs With Postweaning Diarrhea in China - Guo, Liang; Wang, Jing; Wang, Shenghua; Su, Jinhui; Wang, Xue; Zhu, Yaohong (Frontiers in Veterinary Science, 2020)
Diarrheagenic Escherichia coli is the causative agent of diarrhea in infants and animals worldwide. Many isolated strains recovered from pigs with postweaning diarrhea are multidrug resistance (MDR), and hybrids of E. coli are potentially more virulent, as enterotoxigenic E. coli (ETEC)/Shiga-toxigenic E. coli (STEC) hybrids. Here, we used whole-genome sequencing to analyze clinical isolates of the 5 colistin resistance E. coli. The E. coli CAU15104, CAU15134 and CAU16060 belonged to ETEC/STEC hybrids, display the same serotype O3:H45 and sequence type ST4214. The E. coli CAU16175 and CAU16177 belonged to atypical enteropathogenic E. coli (aEPEC), display O4:H11 and O103:H2, ST29 and ST20, respectively. The E. coli CAU16175 carries six plasmids. An IncHI2 type plasmid, pCAU16175_1, harbors an IS26-riched MDR region, which includes sixteen antimicrobial resistance genes. An IncFII type plasmid, pCAU16175_3, harbors mcr-1.1, tet(M) and blaTEM-1B, while mcr-1.1 is located within a Tn2 derivative. Our findings indicate that the ETEC/STEC strains of the O3:H45 serotype as well as the aEPEC strains of the O4:H11 and O103:H2 serotypes are associated with postweaning diarrhea in swine and that some of diarrheagenic E. coli contains IS26-riched MDR region and the mcr-1 gene located within a Tn2 derivative on IncFII plasmid.